Aggregation threshold for Novel Au – LiNbO3 core/shell Nano composite: effect of laser ablation energy fluence - Marwa., S. Alwazny (Universiti Malaysia Perlis (UniMAP), 2022)
Link to publisher's homepage at http://ijneam.unimap.edu.my